DO CAPITAL AO IMPÉRIO: miséria da filosofia política - Flávio Bezerra de Farias (Universidade Federal do Maranhão, 2005)
The passage from the Critique of Political Economy to the Critique of Polities, Cali into question these passage implement by Michael Hardt and Antonio Negri, thin the context of the postmodern era, situated beyond fordism and within globalization.